SOCIAL MOBILITY IN ALAN PARKER'S EVITA (1996): A MARXIST APPROACH - SETIYOWATI, ARIS (2010)
The object of the study is a movie entitled Evita directed by Alan Parker. The problem of this study is how the social mobility of major character is reflected in Evita based on Marxist approach The study in this research paper is descriptive qualitative. The data sources are divided into two, namely primary data sources and secondary data sources. The primary data sources are the movie and script of Evita and the secondary data sources are information related to the primary data sources, books about Marxist approach and website. The techniques of data analysis are observation and library review. The technique of data analysis is descriptive technique. Based on the analysis the researcher shows the conclusion as follows: First, based on the structural analysis Parker in Evita illustrated that "everyone has opportunity to improve his or her life, respect, and fame" in order to deliver the message Parker used real character Eva Duarte Peron who built her career from the bottom. Second, based on Marxist analysis it is evident that Parker illustrate the social mobility of the people at the times of changing.